Coming home: older patients’ and their relatives’ experiences of well-being in the transition from hospital to home after early discharge - Aline Dragosits; Bente Martinsen; Ann Hemingway; Annelise Norlyk (International Journal of Qualitative Studies on Health & Well-Being)
Background This study aims to investigate the lived experience of well-being among older patients and their relatives in the transition from hospital to home after early discharge. Research has shown that the transition brings severe challenges to their everyday lives. However, to date, there has been a lack of research focusing on the lived experiences of well-being during this process. Methods The data collection and analysis followed the phenomenological approach of Reflective Lifeworld Research. Ten in-depth interviews with older patients and their relatives were conducted in Austria up to 2–5 days after hospital discharge. Results The essential meaning of the phenomenon of well-being in the transition from hospital to home is marked by security and confidence to face the challenges following the discharge. Four constituents emerged: being calm and in alignment with the homecoming, being in familiar surroundings at home—a sense of belonging, striving towards independence—continuity of life and having faith in the future. Conclusion Our findings point to the importance of recognizing the vulnerability associated with the transition from hospital to home, as it impacts the existential aspects of space and time. Facilitating a sense of continuity and belonging can foster well-being during this critical period.